Note from the editor - Schutte, Corne (The South African Journal of Industrial Engineering, 2015)
“A dream doesn’t become reality through magic; it takes sweat, determination and hard work.” ― Colin Powel While the contents of this edition has been fixed for nearly two months, the final editing process took time, linked to a very busy time at work. The role of editor is a part time position, working with volunteers as section editors, technical editors, and reviewers. Thus this sometimes needs to take a second priority to other pressing matters. It is therefore very satisfying when we manage to get the journal ready and published on schedule! Due to a more scalable editorial process where we use section editors to manage the review process, and the fact that it reaches most readers electronically, we can therefore aim for editions with more articles per edition. Therefore: This edition has a total of 19 articles, and it is the thickest edition so far as far as we know – nearly 300 pages! Another notable difference in this edition is that the proportion of locally authored articles had increased: of the 19 articles, 14 are from South African authors and 5 from international authors. While international exposure for a journal is a good thing, this is a journal with a regional Southern African focus, sponsored by the Southern African Institute for Industrial Engineering, and we are attempting to publish articles that are of interest to the Industrial Engineering, Engineering Management and related disciplines in this region. Consequently, we are aiming to have a healthy balance of international and local authors publishing here. On a sad note:- The Engineering Faculty at the University of Stellenbosch lost a very promising engineer and researcher in February: Prof Cornie Scheffer. He was also the chairman of the Mechanical and Mechatronic Engineering Department, and a regular contributor to RAPDASA. Consequently we found it fitting to publish as a feature article, an article co-authored by him, as a final tribute to him. If you have suggestions on how we can take this journal forward, please let me know. C.S.L. Schutte: Editor